Factors Associated with Variations in State and Local Government Spending - Bahl, Roy W.; Saunders, Robert J. (Journal of Finance, 1966)
Originally published in: Bahl, Roy W., and Robert J. Saunders. “Factors Associated with Variations in State and Local Government Spending.” The Journal of Finance 21, no. 3 (1966): 523–34. https://doi.org/10.2307/2977827. (c) Wiley. Posted by permission of the publisher.